DOCTORAL STUDENT OF THE KARAKALPAK INSTITUTE OF AGRICULTURE AND AGROTECHNOLOGIES - ORAZIMBETOV EDILBEK KAYPBEKOVICH (TADQIQOTLAR, 2025)
ABSTRACT The  cultivation  of  pumpkin  (Cucurbita  L)  in  the  agro-climatic  conditions  of Karakalpakstan  holds  significant  potential  due  to  the  crop's  adaptability,  drought resistance, and economic value. This study investigates the optimal agrotechnological practices  for  growing  pumpkin  in  arid  and  semi-arid  regions  of  Karakalpakstan, focusing  on  soil  preparation,  irrigation  regimes,  planting  densities,  fertilization systems, and disease resistance. Field trials were conducted over two growing seasons to  evaluate  the  yield,  fruit  quality,  and  resistance  to  abiotic  stress  factors  such  as salinity and high temperatures. The results demonstrate that the use of drip irrigation, organic  mulching,  and  biofertilizers  significantly  enhances  productivity  and  fruit quality. Furthermore, locally adapted pumpkin varieties showed better resilience to environmental  stressors  compared  to  introduced  cultivars.  The  findings  provide  a scientific basis for developing sustainable pumpkin production systems in resource-limited regions, contributing to food security and the diversification of agricultural production in Karakalpakstan.